The influence of principal managerial ability and teacher performance toward senior high school quality - Sowiyah Sowiyah; Zulaikha Fitriyanti; Veronica Eka Desi Natalia (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
The current research aimed to analyze and determine the effect of principal managerial ability and teacher performance on the quality of senior high school in Way Kanan regency. This research is quantitative using a descriptive verification method with a cluster random sampling technique with a sample of 235 teachers of Way Kanan regency. Data were collected using a questionnaire. The collected data were analyzed through multiple equation regression with the help of SPSS Statistics 17 software and then interpreted. The results of this study indicate that there was an influence of principal managerial ability on school quality by 63.7%. In addition, there was an influence of teacher performance on school quality by 58.6%, and finally there was an effect of principal managerial ability and teacher performance on school quality by 68.2%. The implications of the current findings are also discussed.